Bladder Cancer in HIV-infected Adults: An Emerging Issue? Case-Reports and Systematic Review. - Sylvain Chawki; Guillaume Ploussard; Claire Montlahuc; Jérome Verine; Pierre Mongiat-Artus; François Desgrandchamps; Jean-Michel Molina (PLoS ONE)
Objectives Non-AIDS-related malignancies now represent a frequent cause of death among HIV-infected patients. Albeit bladder cancer is one of the most common malignancies worldwide, it has been rarely reported among HIV-infected patients. We wished to assess the prevalence and characteristics of bladder cancer in HIV-infected patients. Methods We conducted a single center retrospective study from 1998 to 2013 in a university hospital in Paris. Cases of bladder cancer among HIV-infected patients were identified using the electronic records of the hospital database and of the HIV-infected cohort. Patient characteristics and outcomes were retrieved from patients charts. A systematic review of published cases of bladder cancers in patients with HIV-infection was also performed. Results During the study period we identified 15 HIV-infected patients (0.2% of the cohort) with a bladder cancer. Patients were mostly men (73%) and smokers (67%), with a median age of 56 years at cancer diagnosis. Bladder cancer was diagnosed a median of 14 years after HIV-infection. Most patients were on ART (86%) with median current and nadir CD4 cell counts of 506 and 195 cells/mm3, respectively. Haematuria (73%) was the most frequent presenting symptom and HPV-associated lesions were seen in 6/10 (60%) patients. Histopathology showed transitional cell carcinoma in 80% and a high proportion of tumors with muscle invasion (47%) and high histologic grade (73%). One-year survival rate was 74.6%. The systematic review identified 13 additional cases of urothelial bladder cancers which shared similar features. Conclusions Bladder cancers in HIV-infected patients remain rare but may occur in relatively young patients with a low nadir CD4 cell count, have aggressive pathological features and can be fatal.